A Case Study of Unpopular Use of Worodwall for English Teaching in SMA Negeri 1 Tanjunganom Nganjuk - Ericha Putri Marchanda; Ahmad Munir (Jurnal Ilmiah Telaah, 2026)
Technology integration for English as a Foreign Language (EFL) instruction was required under the Merdeka curriculum. However, the application of digital learning platforms remained inconsistent. Although Wordwall was known for enhancing vocabulary and grammar instruction, it has demonstrated notable benefits in prior research. However, the adoption remained limited even at schools with adequate ICT infrastructure. Therefore, this qualitative case study aimed to explore specific reasons behind the non-use of Wordwall among English teachers at SMAN 1 Tanjunganom. Data were collected through in-depth interviews and a classroom observation sheet. The findings revealed three main barriers: limited awareness of platform features, unstable internet connectivity, and time limitations in preparing new instructional materials. These obstacles indicated that limited technological knowledge affected technological pedagogical knowledge, preventing teachers from recognizing Wordwall. The research concludes that adequate physical infrastructure alone does not guarantee adoption of digital tools. Ultimately, sustained technology training and reliable internet access were necessary for successful technology integration in EFL classrooms.